EFFECT OF UREA CONCENTRATION ON THE GROWTH OF CELLS OF Nannochloropsis sp. LABORATORY SCALE - Wahyuni, Indri; Nurrachmi, Irvina; Nursyirwani, Nursyirwani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
ABSTRACT This research was conducted from October 2021 to January 2022 in the Natural Feed Laboratory of the Brackish Water Cultivation Fisheries Center (BPBAP) Ujung Batee, Aceh. This study aimed to determine whether urea has an effect and the best urea concentration on the growth of Nannochloropsis sp. This study used an experimental method with one-factor RAL (Completely Randomised Design), consisting of 4 levels of treatment and control with three replications so that 15 experimental units were obtained. The treatments tested were the uses of urea 40 ppm (treatment A), urea 60 ppm (treatment B), urea 80 ppm (treatment C), urea 100 ppm (treatment D), and Walne 1 ml (control). The population density of Nannochlropsis sp. was found in treatment D on day 4 (2414 x 104 cells/mL), and the lowest population growth was shown in treatment A (1177 x 104 cells/mL). The highest absolute growth rate occurred in treatment D (2229x 104 cells/mL), while the highest relative growth rate occurred in treatment D (1205%), and the highest specific growth rate occurred in treatment B (79% per day).